The Students' Perceptions of Using a Zoom Cloud Meeting Application in Online Reading Classes - Yusuf Amri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This research presents the students’ perceptions of using a zoom cloud meeting application in online reading classes. The research used a descriptive qualitative approach with a descriptive study as the research design. The subjects were 33 third-semester students of the English Department of UNISMA Malang. This study used two instruments to obtain the data, the first was a questionnaire consisting of 10 statements, and the second was an interview that used open-ended interviews. The findings of this study showed the students’ perceptions of using a zoom cloud meeting application in taking online reading classes were positive in some aspects, such as enjoying to use, the interest, and challenge, the ease of understanding, and the benefits of using a Zoom Cloud meeting application. Unfortunately, the students’ perceptions in online reading classes were negatively related to the getting some troubles, such as bad internet connection and financial problems in buying internet quota data.Key Words: Students’ Perceptions, Zoom Cloud Meeting, Online Reading Classes